Factors that influence volunteering intention among part six students under Faculty of Business and Management at UiTM Kampus Bandaraya Melaka / Nurul Athirah Mohamad Yadi - Mohamad Yadi, Nurul Athirah (Faculty of Business and Management, 2018)
The aim of this research is to investigate factors that influence volunteering intention among part six students Under Faculty of Business and Management at UiTM Kampus Bandaraya Melaka. There are three objectives under this research which is to examine the relationship between attitude towards intention on volunteering activities, to analyse the relationship between perceived behavioral controls towards intention on volunteering activities, and to determine the relationship between subjective norms towards intention on volunteering activities. This research is using Theory of Planned Behavior and four variables are used under this theory. The Dependent variable is intention on volunteering activities while the independent variables are attitude, perceived behavioral control and subjective norm. To complete this research, three hypotheses are constructed to determine the relationship between the independent variables toward the dependent variable. A total of 289 students are involved to the the respondent and they are among part six students of Business and Management faculty. All the data is collected by using questionnaire. All the data obtained was analysed using Statistical Package for the Sosial Scine (SPSS) Software 22.